Tari Persembahan Bersujud di Kabupaten Tanah Bumbu Kalimantan Selatan - Dini Maulidya (Pelataran Seni, 2016)
AbstractThis study aimed to describe the function and form of Persembahan Bersujud Dance in Tanah Bumbu, South Kalimantan. With descriptive qualitative approach, this research data obtained through observational studies in Tanah Bumbu, interviews with sources and documentation associated with prostration Dance Tribute. The results showed that the function dan form performance Persembahan Bersujud Dance in Tanah Bumbu regency is known as the entertainment on the way-local Goverment official events. In addition, this dance also serves as a medium of education through moral teachings in the lyrics or lyrics accompaniment. Persembahan Bersujud Dance is a new creation dance under the guidance of H. Bakhtiar Sanderta. This dance depicts the peculiarities of society Tanah Bumbu very thick with the influence of Islam and its plurality, that is a mix between Bugis and Banjar tribe.Keywords: persembahan bersujud dance, function, form performances, tanah bumbu